Snow accumulation from the Bryan Coast ice core (BC11), Ellsworth Land, West Antarctica - Thomas, Elizabeth (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
This dataset provides a 298 year (1712-2010) annual snow accumulation record from the Bryan Coast (BC11) ice core. The 140 m core was drilled on the Bryan Coast in Ellsworth Land, West Antarctica, during the austral summer 2010/11. The record was measured using the summer peak in non sea salt (nss) SO4, in approximately January to December. Snow accumulation is converted to meters of water equivalent (weq - m) based on measured density profile and correcting for thinning using the Nye model, assuming vertical strain rate. Samples were measured at 5 cm resolution, corresponding to approximately eight samples per year.